2013
DOI: 10.4236/ojrm.2013.22007
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous administration of adipose-derived stromal cells does not ameliorate bleomycin-induced lung injury in rats

Abstract: Background: Mesenchymal stromal cells (MSCs) have been studied intensively in regenerative medicine. Among MSCs, adipose tissue-derived stromal cells (ASCs) are relatively easy to obtain from a patient. Since ASCs are ideal candidates for use in the treatment of disease states including pulmonary fibrosis, we investigated whether intravenous injection of ASCs could exert a therapeutic effect against bleomycininduced lung injury in rats. Methods: Rats were intratracheally administered bleomycin, and one week la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 34 publications
1
16
0
Order By: Relevance
“…In the present study, we have shown than AD-MSCs are efficacious in ameliorating the symptoms of pulmonary fibrosis by increasing survivability and protection from lung fibrosis comparatively better than pirfenidone. Earlier two studies also showed that AD-MSCs relived IPF and provide significant contribution to lung repair at an early stage of disease (16, 18), however, one study did not show any beneficial effect of intra-venous infusion of AD-MSCs either at 0 day or 14 day post bleomycin challenge in lung repair (27). Many studies have reported beneficial effects from MSCs derived from bone marrow, umbilical cord, and amniotic fluid for bleomycin induced lung injury in mice or rat model (2830).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the present study, we have shown than AD-MSCs are efficacious in ameliorating the symptoms of pulmonary fibrosis by increasing survivability and protection from lung fibrosis comparatively better than pirfenidone. Earlier two studies also showed that AD-MSCs relived IPF and provide significant contribution to lung repair at an early stage of disease (16, 18), however, one study did not show any beneficial effect of intra-venous infusion of AD-MSCs either at 0 day or 14 day post bleomycin challenge in lung repair (27). Many studies have reported beneficial effects from MSCs derived from bone marrow, umbilical cord, and amniotic fluid for bleomycin induced lung injury in mice or rat model (2830).…”
Section: Discussionmentioning
confidence: 99%
“…There is no available data suggesting that MSC administration once fibrosis is established will decrease fibrosis, rather several studies suggested that MSCs administration at the fibrotic lungs may not be effective, rather may increase lung fibrosis (27, 38, 39). Our attempt to infuse AD-MSC at fibrotic stage on day 14, 17 and 20 post bleomycin did not yield any results since most of the animals did not survive (data not shown).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, ADSCs-SVF, were neither cultured nor expanded and were directly infused within the patients’ lungs after implementing a two-step activation procedure using a cocktail of autologous growth factors (PRP) [50] and photobiostimulation [51], two novel approaches known to amplify paracrine beneficial effects of MSCs. Furthermore, recent preclinical and human studies have raised significant concerns with regards to possible dysfunctional migratory and paracrine properties of ADSCs-SVF derived from older individuals [60] and mice [61]. In particular, Uji et al [61] recently reported that stromal cells derived from the adipose tissue of relatively older mice exhibited reduced migratory capacity and failed to attenuate bleomycin-induced lung fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, recent preclinical and human studies have raised significant concerns with regards to possible dysfunctional migratory and paracrine properties of ADSCs-SVF derived from older individuals [60] and mice [61]. In particular, Uji et al [61] recently reported that stromal cells derived from the adipose tissue of relatively older mice exhibited reduced migratory capacity and failed to attenuate bleomycin-induced lung fibrosis. While the subject of an ongoing study, cultures of ADSCs-SVF derived from representative patients with IPF revealed a significant increase in the number of ADSCs-SVF colonies and an overexpression of anti-inflammatory (IL1-receptor antagonist) and angiogenic (vascular endothelial growth factor-VEGF) mediators, following activation with PRP and laser irradiation.…”
Section: Discussionmentioning
confidence: 99%